Optimalisasi Perlindungan Jaminan Sosial untuk Pekerja Informal melalui Inovasi Layanan dan Digitalisasi Keuangan - Asep Dadan Suhendar; Rima Kania; Muhammad Abdul Wakil (Journal of Empowerment Community, 2026)
Social security protection for informal workers remains a major challenge in achieving labor welfare in Indonesia. This study aims to analyze efforts to optimize social security protection for informal workers in the Indramayu region through the BPJS Ketenagakerjaan program. The research method used is descriptive qualitative with a field study approach, involving interviews and observations with informal workers, and BPJS Ketenagakerjaan Indramayu Branch officers. The results show that the participation rate of informal workers is still relatively low due to limited understanding of social security benefits, economic constraints, and the lack of continuous socialization. Optimization efforts are carried out through service innovation in improving public education, collaboration with local governments and worker communities, and strengthening the role of PERISAI agents as the frontline in participant acquisition and financial digitization for ease of transactions. In conclusion, increasing awareness and participation of informal workers in social security requires intensive communication strategies and sustainable policy support to achieve comprehensive social protection in the Indramayu region.